KONSEP DAN RUANG LINGKUP GOOD CORPORATE GOVERNANCE - Moventa Alfredo; Rilla Masyita; Vania Khairunisa Lubis; Ahmad Wahyudi Zein (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the concept and implementation of Good Corporate Governance (GCG) and its relevance in addressing agency conflicts through theoretical review and the Enron case study. The research employs a library research method, examining theories, regulations, and literature related to GCG. Data were analyzed qualitatively and descriptively to understand how the principles of transparency, accountability, responsibility, independence, and fairness function to prevent governance misconduct. The findings indicate that consistent implementation of GCG strengthens public trust, enhances managerial accountability, and prevents financial manipulation, as demonstrated by the Enron scandal. This study highlights the necessity of strengthening corporate governance to create sustainable value and reduce financial and operational risks.